Disrupted topological properties of the structural brain network in patients with cerebellar infarction on different sides are associated with cognitive impairment - Wang, Duohao; Yao, Qun; Lin, Xingjian; Hu, Jun; Shi, Jingping (Frontiers in Neurology, 2022)
Purpose To explore changes in the brain structural network in patients with cerebellar infarction on different sides and their correlations with changes in cognitive function. Method Nineteen patients with acute left posterior cerebellar infarction and 18 patients with acute right posterior cerebellar infarction seen from July 2016 to September 2019 in the Department of Neurology, Affiliated Brain Hospital of Nanjing Medical University, were selected. A total of 27 healthy controls matched for sex, age, and years of education were recruited. The subjects underwent head diffusion magnetic resonance imaging examination and neuropsychological cognitive scale evaluation, and we analysed changes in brain structural network properties in patients with cerebellar infarction and their correlation with changes in patients' cognitive function. Result MMSE, MOCA and RAVLT scores in the left and right cerebellar infarction groups were significantly lower than those in the healthy control group (P<0.05). In addition, DST scores were lower in the left cerebellar infarction group (P<0.05); TMT times in the right cerebellar infarction group were significantly higher than those in the left cerebellar infarction group (P<0.05). Meanwhile, the left and right cerebellar infarction groups had abnormal brain topological properties, including clustering coefficient, shortest path length, global efficiency, local efficiency and nodal efficiency. After unilateral cerebellar infarction, bilateral cerebral nodal efficiency was abnormal. Correlation analysis showed that there was a close correlation between decreased processing speed in patients with left cerebellar infarction and decreased efficiency of right cerebral nodes (P<0.05), and there was a close relationship between executive dysfunction and decreased efficiency of left cerebral nodes in patients with right cerebellar infarction (P<0.05). Conclusion Patients with cerebellar infarction have cognitive impairment. Unilateral cerebellar infarction can reduce the network efficiency of key regions in the bilateral cerebral hemispheres, and these abnormal changes are closely related to patient cognitive impairment. The results of this study provide evidence for understanding the underlying neural mechanisms of cerebellar cognitive impairment and suggest that brain topological network properties may be markers of cerebellar cognitive impairment.